2013
DOI: 10.1111/jog.12037
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic findings after vaginal gauze packing: New insight into an old technique

Abstract: We had a transferred case of cervical ectopic pregnancy with hemorrhagic shock at 6 weeks of gestation. Upon arrival at hospital, we performed tight and full vaginal gauze packing to push the uterus upward to control the patient's hemorrhage. Following stabilization of her general condition, she was treated with uterine artery embolization. Using angiography, the effectiveness of vaginal gauze packing for emergency hemostasis by the presumed mechanism of impairing blood flow through the uterine artery was demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It was previously reported that uterine bleeding might occur with adenomyosis, especially when dienogest was administered, as in the present case . The treatment options for uterine bleeding include pharmacological treatment, angiographic embolization, balloon tamponade, gauze packing, and hysterectomy . If the bleeding cannot be controlled using less invasive procedures, hysterectomy is required to achieve definitive hemostasis.…”
Section: Discussionmentioning
confidence: 65%
“…It was previously reported that uterine bleeding might occur with adenomyosis, especially when dienogest was administered, as in the present case . The treatment options for uterine bleeding include pharmacological treatment, angiographic embolization, balloon tamponade, gauze packing, and hysterectomy . If the bleeding cannot be controlled using less invasive procedures, hysterectomy is required to achieve definitive hemostasis.…”
Section: Discussionmentioning
confidence: 65%
“…The mechanism of hemostasis probably depended on two mechanisms: 1) flask lower uterine segments compressed between the well contracted uterine fundus and vaginal packing, and 2) due to impaired blood flow through the uterine artery owing to an elevated uterus. Koyama et al's findings suggested a second mechanism (12). Compressing the uterus may lead to elongated and curved uterine arteries in a vertical direction, a narrowing of intravascular space and obstructing the vessels, and the reduction of uterine blood flow.…”
Section: Discussionmentioning
confidence: 99%